Efforts to Increase the Sense of Nationalism Through Bhineka's Careful Comic Media: Upaya Peningkatan Rasa Nasionalisme Melalui Media KCB (Komik Cermat Bhineka) - Maylaffaiza Maylaffaiza; Suci Perwita Sari (ITScience (Information Technology and Science), 2025)
This study aims to find out efforts to increase the sense of nationalism through the comic media Cermat Bhineka at the 'Aisyiyah Pandan Guidance Studio, Malaysia. Nationalism is an important value in the formation of national identity that must be instilled in the younger generation, especially in a multicultural context. Cermat Bhineka's comic media was chosen as a tool to convey national messages in a more interesting and easy-to-understand way for children. This study uses a qualitative approach with the classroom action research method, which involves planning, implementation, observation, and reflection activities in certain cycles. Data were collected through observation, interviews, and documentation during the learning process at the 'Aisyiyah Pandan Guidance Center. With the subject, namely 22 students. The results of the study showed that there was a significant increase in students' sense of nationalism after the implementation of Cermat Bhineka's comic media. At the pre-action stage, most of the students were in the low category, with a percentage of 41.4%. However, after the application of the Cermat Bhineka comic in Cycle I, there was an increase with a better average score of 60.8%. Further improvements were recorded in Cycle II, where all students were in the high category with an average excellent score of 85.3%. In addition, the assessment of the practicality of Cermat Bhineka's comic media showed that the use of this media was very practical in improving student understanding, with the percentage of practicality reaching 90.75%. The use of Cermat Bhineka comics can increase students' understanding and sense of nationalism, which is reflected in increased participation, discussion, and appreciation of cultural diversity and national values. Based on these findings, it is recommended that comic media continue to be developed and used as one of the learning methods to arouse the spirit of nationalism in the younger generation, especially in a multicultural environment such as Malaysia.